Medication use by adults in greater Manaus: a population-based cross-sectional study, 2015 - Vanessa Gomes Lima; Marcus Tolentino Silva; Taís Freire Galvão (Universidade de São Paulo, 2021)
The use of medicines can be an indicator of healthcare access. Our aim was to evaluate the consumption of medicine and associated factors among adults in Manaus Metropolitan Region, located in the north of Brazil. A cross-sectional population-based study was conducted with adults, ≥18 years old, selected by probabilistic sampling. The outcome was the use of medicine in the previous 15 days. Poisson regression with robust variance was used to calculate the prevalence ratio (PR) of medicine consumption, with 95% confidence interval (CI). Use of medicines was reported by 29% (95% CI: 28-31%) of the participants. People with good (PR: 0.82, 95% CI: 0.72-0.94) and fair (PR: 0.77, 95% CI: 0.65-0.90) health status were shown to use less medication than those with very good health. People with partners (PR: 1.19, 95% CI: 1.08-1.31), and people who had sought healthcare service in the fortnight (PR: 2.16, 95% CI: 1.97-2.37) showed higher medicine consumption. Medical prescription (80.1%) was the main inductor of consumption; purchasing at a drug store (46.4%), and acquiring through the Brazilian Unified Health System (39.6%) were the main ways to obtain medicines. About one-third of adults in the Metropolitan Region of Manaus used medicines regularly, mainly people with very good health, living with partners, and with recent use of a health service.